Functional Material Systems for Stimuli-Responsive Interference Coloration - (:unkn) unknown (My University, 2021)
Part I: Responsive Interference Coloration (RIC) Systems for High-Performance Humidity Sensing High-humidity conditions (85−100% relative humidity) have a variety of effects on many aspects of our daily lives. In spite of significant progress in the development of structural coloration-based humidity sensors, enhancing the sensitivity and visual humidity resolution of these sensors at high-humidity environment remains a big challenge. In this work, high-performance colorimetric humidity sensors based on environment-friendly konjac glucomannan (KGM) are introduced. These sensors are fabricated via thin-film interference and prepared using a simple, affordable, and scalable method. An effective approach is shown for markedly improving the sensitivity and visual humidity resolution of the sensors under high-humidity environments. This approach takes advantage of synergistic integration of multi-order interference peaks, sensor array technology, and a superior water-absorbing polymer layer. The resulting KGM sensors exhibit full-range humidity sensing and provide rapid and dynamic response toward humidity changes without power consumption. In addition, the sensors exhibit high sensitivity and selectivity, little hysteresis, and excellent stability against high-humidity environments. An extraordinary red reflection peak shift (e.g., 385 nm) and the visual humidity resolution as high as 1.5% RH in the visible range from 85 to 100% RH is observed for the KGM sensors. These values represent the largest spectral shift and highest visual humidity resolution, respectively, for structural coloration-based humidity sensors in high-humidity conditions. Part II: Responsive Interference Coloration (RIC) Systems for Chemical Vapors Sensing Volatile organic compounds (VOCs) are generated by a wide array of sources and can contribute to the development of numerous health-related problems. Resolving the potential risks related to the VOCs exposure primarily needs accurate qualitative and quantitative measurements of these compounds both in indoor and outdoor environments. The detection of VOCs in ambient conditions is a challenging task, however, since several difficulties are involved in analytical quantification techniques. Colorimetric sensing of volatile organic compounds has been extensively reported using a wide range of materials for capturing the target molecules, including organic dyes, metal-organic frameworks, and polymers. In this study, colorimetric VOC sensors based on polystyrene (PS) and Nafion are introduced. The sensors are fabricated via thin-film interference and prepared using a simple, affordable, and scalable method. A sensor array approach is applied for improving the sensitivity of the sensors upon exposure to various organic compounds. The sensors show rapid and dynamic response towards VOC vapors, along with reasonable selectivity against various analytes. Polystyrene-RIC sensors display sensitivity of ~ 64 μg/mL when exposed to toluene vapor. By integration of various PS sensors into a single array, multianalyte recognition can be realized, with only one RIC material of different thicknesses. The Nafion-RIC sensors display sensitivity of ~ 14-15 μg/mL when exposed to ethanol and isopropanol vapors, respectively. By integration of various Nafion sensors into a single array, multianalyte recognition can be realized, with only one RIC material of different thicknesses. Data for selective sensing of alcohols are rather promising, since the Nafion sensor is capable of distinguishing between several alcohols with similar chemical structures (i.e., methanol and ethanol).
Keywords: colorimetric sensor; humidity sensor; structural color; thin-film interference